Pharmacological lipid-modification therapies for prevention of ischaemic heart disease: current and future options. Issue 10199 (24th August 2019) - Ray, Kausik K; Corral, Pablo; Morales, Enrique; Nicholls, Stephen J
Summary: Atherosclerosis and its clinical manifestation as ischaemic heart disease remains a considerable health burden. Given that many factors contribute to ischaemic heart disease, a multifactorial approach to prevention is recommended, starting with lifestyle advice, smoking cessation, and control of known cardiovascular risk factors, such as blood pressure and lipids. Within the lipid profile, the principal target is lowering LDL cholesterol, firstly with lifestyle interventions and subsequently with pharmacological therapy. Statins are the recommended first-line pharmacological treatment. Some individuals might require further lowering of LDL cholesterol or be unable to tolerate statins. Additional therapies targeting different pathways in cholesterol metabolism are now available, ranging from small molecules taken orally, to injectable therapies. Examples include ezetimibe, which targets Niemann-Pick C1-like protein, and monoclonal antibodies that target PCSK9. Phase 3 trials have also been completed for bempedoic acid (targeting ATP-citrate lyase) and inclisiran (an interference RNA-based therapeutic targeting hepatic PCSK9 synthesis). In addition to LDL cholesterol, mendelian randomisation studies support a causal role for lipoprotein(a) and triglycerides in ischaemic heart disease. In this Series paper, we appraise currently available and emerging therapies for lowering LDL cholesterol, lipoprotein(a), and triglycerides for prevention of ischaemic heart disease.